Privacy-preserving maximum value determination scheme - Hou, Min; Wu, Yue (Frontiers in Physics, 2025)
This paper introduces a quantum-secure scheme for conducting privacy-preserving maximum value determination, allowing the parties to ascertain the highest value from their confidential inputs while keeping non-maximum data private. Participants first transform their private inputs into binary representations and then apply local operations to encode these values into quantum states. These encoded states are transmitted to a semi-trusted intermediary, which computes the maximum through quantum–mechanical interactions. The protocol is designed to ensure confidentiality against potential external threats, including quantum attack strategies such as intercept-resend, entangle-measure, and Trojan horse attacks, while also preventing any disclosure of inputs between the participants. The framework is practical, utilizing entangled Bell states as carriers of information, leveraging quantum state manipulations for secure encoding, and employing quantum measurements for result extraction. Empirical results obtained from simulations using IBM Quantum Composer demonstrate the operational feasibility of the scheme. A correctness analysis indicates that if the participants accurately submit their respective inputs and adhere strictly to the protocol, the semi-trusted intermediary will reliably reveal the maximum value to both parties. Additionally, fairness is ensured through the intermediary’s role in disclosing the maximum value simultaneously to both parties, preventing any unfair advantage.